Revitalizing Classroom Attendance: Reviving Interest in Medical Education by Tackling Challenges and Embracing Solutions (GAIMS Journal of Medical Sciences, 2023)
The pursuit of medical education has always been a noble path, attracting individuals driven by a passion to heal, serve, and make a meaningful impact on society. However, in recent years, there has been a concerning decline in classroom attendance among undergraduate medical students. The significance of in-person learning cannot be understated, as it facilitates hands-on experience, fosters mentorship, and enables collaborative learning. To ensure the future of medicine remains bright, it is imperative to address the challenges leading to decreased classroom attendance and implement effective solutions that reignite interest in medical education. This editorial delves into the underlying issues and proposes measures to revitalize classroom attendance and rekindle enthusiasm in the pursuit of medical knowledge.